2019
DOI: 10.2147/jaa.s186252
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association of genetic variants with level of asthma control in the Arab population</p>

Abstract: BackgroundRates of asthma in Jordan have been doubled in the past decade, but this increased prevalence was not met with improved asthma control protocols. The aim of the present study was to assess whether there was any significant association between the level of asthma control and certain single-nucleotide polymorphisms (SNPs) in five genes: (ADRB2; rs1042713 and rs1042714), (CRHR1; rs1876828, rs242939, and rs242941), (STIP1; rs2236647), (ADH5, rs1154400), and (ARG1; rs2781659). These SNPs were selected bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…An association of the rs2781666*T allele and CT haplotype (rs60389358, rs2781666) of the ARG1 gene with asthma and a considerably higher level of serum arginase was established in asthma patients from India (Donthi et al, 2018). On the contrary, some studies did not detect a significant association of ARG1 gene polymorphisms with the efficacy of asthma therapies (Almomani et al, 2019;Scaparrotta et al, 2019). Together, this results and literature data confirm that ARG1 gene allelic variants can contribute to asthma pathogenesis and the effectiveness of disease therapy.…”
Section: Discussionsupporting
confidence: 55%
“…An association of the rs2781666*T allele and CT haplotype (rs60389358, rs2781666) of the ARG1 gene with asthma and a considerably higher level of serum arginase was established in asthma patients from India (Donthi et al, 2018). On the contrary, some studies did not detect a significant association of ARG1 gene polymorphisms with the efficacy of asthma therapies (Almomani et al, 2019;Scaparrotta et al, 2019). Together, this results and literature data confirm that ARG1 gene allelic variants can contribute to asthma pathogenesis and the effectiveness of disease therapy.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, only 30% of the adult patients that took part in a recent Jordanian study were reported to have achieved asthma control [20]. A study from northern of Jordan showed that smoking is the main cause of poor asthma control in adolescent[4] and two studies from Jordan attributed poor control to non-adherence or improper use of inhalers [21, 22]; moreover one study showed a significant association between the level of asthma control and genetic in Arab population [23]. However, this issue is rarely investigated in the south of Jordan and the burden of uncontrolled asthma on patients is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…No relationship was revealed between the increased risk of uncontrolled asthma and the Arg16 allele in asthma patients using ICS and/or LABA. Additionally, Almomani et al reported that the Arg16 allele of Arg16Gly polymorphism is more common among patients with uncontrolled asthma in the Arab population. The influence of Arg16Gly polymorphism on asthma control could be related to impaired ADRB2 function because the presence of arginine instead of glycine in its structure in the 16th amino acid position.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed characterisation of asthma patients contributes to the investigation of the disease pathogenesis, selection of the most optimal therapeutic approaches, monitoring the treatment effectiveness and assessing the risk of disease progression . Arg16Gly and Gln27Glu ADRB2 gene polymorphisms showed association with intermediate asthma phenotypes: nocturnal, severe, uncontrolled, therapy‐resistant and atopic . The most frequent asthma endotype is type 2 asthma .…”
Section: Discussionmentioning
confidence: 99%